Diet-Induced Muscle Insulin Resistance Is Associated With Extracellular Matrix Remodeling and Interaction With Integrin α(2)β(1) in Mice - Kang, Li (American Diabetes Association, 2011)
OBJECTIVE: The hypothesis that high-fat (HF) feeding causes skeletal muscle extracellular matrix (ECM) remodeling in C57BL/6J mice and that this remodeling contributes to diet-induced muscle insulin resistance (IR) through the collagen receptor integrin α(2)β(1) was tested. RESEARCH DESIGN AND METHODS: The association between IR and ECM remodeling was studied in mice fed chow or HF diet. Specific genetic and pharmacological murine models were used to study effects of HF feeding on ECM in the absence of IR. The role of ECM-integrin interaction in IR was studied using hyperinsulinemic-euglycemic clamps on integrin α(2)β(1)-null (itga2(−/−)), integrin α(1)β(1)-null (itga1(−/−)), and wild-type littermate mice fed chow or HF. Integrin α(2)β(1) and integrin α(1)β(1) signaling pathways have opposing actions. RESULTS: HF-fed mice had IR and increased muscle collagen (Col) III and ColIV protein; the former was associated with increased transcript, whereas the latter was associated with reduced matrix metalloproteinase 9 activity. Rescue of muscle IR by genetic muscle-specific mitochondria-targeted catalase overexpression or by the phosphodiesterase 5a inhibitor, sildenafil, reversed HF feeding effects on ECM remodeling and increased muscle vascularity. Collagen remained elevated in HF-fed itga2(−/−) mice. Nevertheless, muscle insulin action and vascularity were increased. Muscle IR in HF-fed itga1(−/−) mice was unchanged. Insulin sensitivity in chow-fed itga1(−/−) and itga2(−/−) mice was not different from wild-type littermates. CONCLUSIONS: ECM collagen expansion is tightly associated with muscle IR. Studies with itga2(−)(/)(−) mice provide mechanistic insight for this association by showing that the link between muscle IR and increased collagen can be uncoupled by the absence of collagen-integrin α(2)β(1) interaction.